2022
DOI: 10.1177/00111287221122755
|View full text |Cite
|
Sign up to set email alerts
|

Youth Mental Health Diversion at Court: Barriers to Diversion and Impact on Reoffending

Abstract: In a cohort of young people referred to an Australian mental health court diversion service over a 7-year period, 46.5% of those deemed eligible ( n = 523) were granted diversion and the following were identified as barriers to being granted diversion: identifying as Aboriginal and/or Torres Strait Islander, having substance use problems, prior offending, and no record of prior diversion. Young people granted diversion were significantly less likely to reoffend, even after adjustment for a range of other covar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
(58 reference statements)
0
5
0
Order By: Relevance
“…In a cohort of young offenders referred to a NSW mental health court diversion service over a 7-year period, 46.5% of those deemed eligible ( n = 523) were granted diversion to community mental health treatment. 30 Young people granted diversion were significantly less likely to reoffend, even after adjustment for a range of other covariates. This effect was evident for both ‘any’ reoffending and for violent reoffending.…”
Section: Economic Benefits Of Trauma-informed First Responders and Di...mentioning
confidence: 95%
“…In a cohort of young offenders referred to a NSW mental health court diversion service over a 7-year period, 46.5% of those deemed eligible ( n = 523) were granted diversion to community mental health treatment. 30 Young people granted diversion were significantly less likely to reoffend, even after adjustment for a range of other covariates. This effect was evident for both ‘any’ reoffending and for violent reoffending.…”
Section: Economic Benefits Of Trauma-informed First Responders and Di...mentioning
confidence: 95%
“…A recent study in New South Wales found that diverting youth with non-SUD diagnoses to community-based mental health treatment can significantly decrease reoffending rates. 3 However, identification as Aboriginal and/or Torres Strait Islander was linked to lower diversion rates. 3 Previous research shows that youth with complex presentations, such as SUDs, co-occurring non-SUDs, and forensic history, benefited the most and completed the Queensland-only state-wide youth voluntary adolescent drug and alcohol withdrawal service program.…”
mentioning
confidence: 99%
“…3 However, identification as Aboriginal and/or Torres Strait Islander was linked to lower diversion rates. 3 Previous research shows that youth with complex presentations, such as SUDs, co-occurring non-SUDs, and forensic history, benefited the most and completed the Queensland-only state-wide youth voluntary adolescent drug and alcohol withdrawal service program. 4,5 The multidisciplinary approach of this service and the provision of culturally appropriate trauma-informed care has led to good outcomes for both the individual and their families and the community.…”
mentioning
confidence: 99%
See 2 more Smart Citations